A community outbreak of food-borne small round-structured virus gastroenteritis caused by a contaminated water supply. - Brugha, R. (Cambridge University Press, 1999)
In August 1994, 30 of 135 (23%) bakery plant employees and over 100 people from South Wales and Bristol in the United Kingdom, were affected by an outbreak of gastroenteritis. Epidemiological studies of employees and three community clusters found illness in employees to be associated with drinking cold water at the bakery (relative risk 3.3, 95%, CI 1.6-7.0), and in community cases with eating custard slices (relative risk 19.8, 95%, CI 2.9-135.1) from a variety of stores supplied by one particular bakery. Small round-structured viruses (SRSV) were identified in stool specimens from 4 employees and 7 community cases. Analysis of the polymerase and capsid regions of the SRSV genome by reverse transcription-polymerase chain reaction (RT-PCR) demonstrated viruses of both genogroups (1 and 2) each with several different nucleotide sequences. The heterogeneity of the viruses identified in the outbreak suggests that dried custard mix may have been inadvertently reconstituted with contaminated water. The incident shows how secondary food contamination can cause wide-scale community gastroenteritis outbreaks, and demonstrates the ability of molecular techniques to support classical epidemiological methods in outbreak investigations.